Effectiveness Of The Cooperative Learning Model Type Teams Games Tournament (TGT) On Learning Outcomes In Basketball Learning - Shofa, Karina Zahara; Suroto, Suroto (Jurnal Pendidikan Jasmani (JPJ), 2024)
Physical Education, Sports, and Health (PJOK) learning has problems, namely a decrease in the level of physical activity, motor skills, and healthy lifestyles of students. This can be caused by the very low level of student participation in participating in PJOK learning. The learning model is an important thing that must be present during learning. Determining the right learning model can also affect the effectiveness or ineffectiveness of a learning process. This study aims to determine whether there is a difference in learning outcomes after implementing the cooperative learning model of the teams games tournament (TGT) type in basketball games. The study was conducted at SMKN 2 Surabaya which is located at Jl. Tentara Genie Pelajar No. 26, Petemon Village, Sawahan District, Surabaya City, East Java. This study uses a quantitative approach of the pre-experimental type (weak experiment) as well as test and measurement techniques to evaluate learning outcomes and questionnaires in identifying student responses to learning. The test results were then analyzed using a descriptive test by converting the values into t-scores first and then analyzing them using the Wilcoxon Test to determine whether there was a difference between the pre-test and post-test values. Based on the results of the analysis, the results of the shooting test assessment showed an insignificant difference with an Asymp. Sig (0.974> 0.05). The results of the dribbling test assessment showed an insignificant difference with an Asymp. Sig (0.991> 0.05). The results of the passing test assessment showed an insignificant difference with an Asymp. Sig (0.991> 0.05). However, the results of the knowledge assessment test showed a significant difference with an Asymp. Sig (0.010 < 0.05). And the average percentage frequency of students who gave positive responses to the effectiveness questionnaire was 94.09%.